Collected Works of Oscar Wilde : The Plays, the Poems, the Stories and the Essays, Including De Profundis - Wilde, Oscar (Ware, Hertfordshire Wordsworth Editions, 1997)
Here is a collection of this witty and irreverent author's works--all in their most authoritative texts. Includes The Picture of Dorian Gray, The Importance of Being Earnest, and other stories and essays
Keywords: English literature -- English literature -- 19th century